Management And Transition Mechanism Of Land PT. Kawasan Industri Wijayakusuma (Persero) Of Semarang City - Andhika Buana Prasadhana; Widya Putri Idayatama; Anis Mashdurohatun (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The study